2017
DOI: 10.1016/j.physa.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

High pressures in room evacuation processes and a first approach to the dynamics around unconscious pedestrians

Abstract: Clogging raises as the principal phenomenon during many evacuation processes of pedestrians in a panic situation. As people push to escape from danger, compression forces may increase to harming levels. Many individuals might fall down, while others will try to dodge the fallen people, or, simply pass through them. We studied the dynamics of the crowd for these situations, in the context of the "social force model". We modeled the unconscious (fallen) pedestrians as inanimate bodies that can be dodged (or not)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…Scenarios described in Refs. [10,11,12] required, however, a step up implementation although sustaining the basic model and its parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Scenarios described in Refs. [10,11,12] required, however, a step up implementation although sustaining the basic model and its parameters.…”
Section: Introductionmentioning
confidence: 99%
“…We calculated the fraction of agents that withstand fatal pressures according to the criteria introduced in Ref. [53]. We found that the vestibule reduces the fraction of agents exposed to dangerous pressures.…”
Section: The Three-entry Vestibulementioning
confidence: 99%
“…[29]. Also, the compression coefficient κ n was set equal to 2.62 × 10 4 N m −1 , according to the experimental value of the human torso stiffness [30].…”
Section: Numerical Simulationsmentioning
confidence: 99%